Environmental Transmission of Typhoid Fever in an Urban Slum. - Adam Akullian; Eric Ng'eno; Alastair I Matheson; Leonard Cosmas; Daniel Macharia; Barry Fields; Godfrey Bigogo; Maina Mugoh; Grace John-Stewart; Judd L Walson; Jonathan Wakefield; Joel M Montgomery (Public Library of Science (PLoS), 2015)
BACKGROUND:Enteric fever due to Salmonella Typhi (typhoid fever) occurs in urban areas with poor sanitation. While direct fecal-oral transmission is thought to be the predominant mode of transmission, recent evidence suggests that indirect environmental transmission may also contribute to disease spread. METHODS:Data from a population-based infectious disease surveillance system (28,000 individuals followed biweekly) were used to map the spatial pattern of typhoid fever in Kibera, an urban informal settlement in Nairobi Kenya, between 2010-2011. Spatial modeling was used to test whether variations in topography and accumulation of surface water explain the geographic patterns of risk. RESULTS:Among children less than ten years of age, risk of typhoid fever was geographically heterogeneous across the study area (p = 0.016) and was positively associated with lower elevation, OR = 1.87, 95% CI (1.36-2.57), p <0.001. In contrast, the risk of typhoid fever did not vary geographically or with elevation among individuals more than ten years of age [corrected]. CONCLUSIONS:Our results provide evidence of indirect, environmental transmission of typhoid fever among children, a group with high exposure to fecal pathogens in the environment. Spatially targeting sanitation interventions may decrease enteric fever transmission.